Cimetidine in patients with gastric ulcer: a multicentre controlled trial. Issue 6090 (24th September 1977) - Frost, F; Rahbek, I; Rune, S J; Jensen, K B; Gudmand-Hoyer, E; Krag, E; Rask-Madsen, J; Wulff, H R; Garbol, J; Jensen, K G; Hojlund, M; Nissen, V R
Abstract : Forty-five adult outpatients with endoscopically confirmed gastric ulceration completed a double-blind trial of either cimetidine (1 g/day) or placebo. After six weeks 18 of the 23 patients receiving cimetidine showed complete ulcer healing compared with only six of the 22 patients receiving placebo. The cimetidine group also had fewer days with pain than the placebo group but the difference was not statistically significant. Cimetidine therefore seems to promote healing of gastric ulcers without severe side effects, although its effect on pain is less pronounced than in patients with duodenal ulcers.